Infundibular pituitary origin syndrome - González Olaechea, Max (1918)
With the name of infundibular syndrome, CLAUDE H. and J. LHERMITTE have pretended identify symptomatic group, whose pathological location would be in the bottom of the third ventricle called infundibulum and pathophysiological manifestations which would be constituted: by disturbances of circulation (tachycardia, extrasystoles), the function of sleep (narcolepsy) and regulation orgaaisrno water (polydipsia, polyuria).